Oxidation of Organic Substrates by Trimethylammonium Halochromates(VI), (CH3)3NH[CrO3X], (X = F, Cl) on Silica Gel - HASSANI JOSHAGHANI, ALI; GHAMMAMY, SHAHRIARE (Asian Journal of Chemistry, 2010)
Silica gel absorbed trimethylammonium fluorochromate (VI), (TriMAFC), (CH3)3NHCrO3F and trimethylammonium chlorochromate(VI), (TriMACC), (CH3)3NHCrO3Cl are efficient and new reagents, which prepare easily and oxidize thiols to the corresponding disulfides quickly. The reactions perform cleanly and controlled to stop at the disulfide stage without over-oxidation side products. The easy procedure, simple work-up, short reaction times and excellent yields are another advantages of these reagents.